Comparative efficacy and safety of rhTPO, romiplostim, and eltrombopag in the treatment of pediatric primary immune thrombocytopenia: a systematic review and network meta-analysis - Zhang, Xiaofang; Zhao, Yuan; Yang, Minghang; Feng, Xiaochun (Frontiers in Immunology, 2025)
BackgroundPediatric primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by isolated thrombocytopenia and an increased risk of bleeding. Conventional therapies, while effective in some cases, are often limited by suboptimal response rates and significant adverse effects with prolonged use. Thrombopoietin receptor agonists (TPO-RAs), including recombinant human thrombopoietin (rhTPO), romiplostim, and eltrombopag, have emerged as promising therapeutic alternatives for pediatric ITP. However, a comprehensive comparison of their efficacy and safety profiles remains lacking.ObjectiveTo conduct a systematic review and network meta-analysis to evaluate and compare the efficacy and safety of rhTPO, romiplostim, and eltrombopag in the treatment of pediatric ITP.MethodsA systematic literature search was performed across PubMed, Embase, Cochrane Library, and other relevant databases. Seven randomized controlled trials (RCTs) involving a total of 375 pediatric ITP patients were included. Direct meta-analysis and Bayesian network meta-analysis were employed to assess overall response rates (ORR) and the incidence of serious adverse events (SAEs). The Surface Under the Cumulative Ranking Curve (SUCRA) was utilized to rank the interventions based on their efficacy and safety.ResultsDirect meta-analysis demonstrated that romiplostim (OR = 17.57, 95% CI: 4.90–63.03), eltrombopag (OR = 5.34, 95% CI: 2.50–11.39), and rhTPO (OR = 5.32, 95% CI: 2.03–13.96) were all significantly more effective than placebo in achieving ORR (P < 0.001). In terms of SAEs, romiplostim was associated with a higher risk (OR = 3.79, 95% CI: 0.66–21.85), whereas eltrombopag (OR = 0.68, 95% CI: 0.23–2.03) and rhTPO (OR = 0.28, 95% CI: 0.01–7.17) exhibited more favorable safety profiles. Network meta-analysis ranked romiplostim (SUCRA = 0.96) as the most efficacious intervention, followed by eltrombopag (0.52) and rhTPO (0.52). For safety, rhTPO (SUCRA = 0.78) ranked highest, followed by eltrombopag (0.66), while romiplostim (0.12) was associated with the highest risk.ConclusionRomiplostim exhibits superior efficacy in the management of pediatric ITP but necessitates vigilant monitoring for potential adverse effects, including bone marrow fibrosis. rhTPO, with its favorable safety profile, is particularly well-suited for acute bleeding scenarios. Eltrombopag offers a balanced combination of oral convenience and safety, making it an optimal choice for long-term therapy. Clinical decision-making should be guided by individual patient factors, including bleeding risk, treatment adherence, and drug accessibility. Future research should prioritize head-to-head comparative trials and long-term follow-up studies to further refine therapeutic strategies and optimize outcomes in pediatric ITP.